Effects of an Endophytic Fungus Umbelopsis dimorpha on the Secondary Metabolites of Host–Plant Kadsura angustifolia - Qin, Dan; Wang, Ling; Han, Meijun; Wang, Junqi; Song, Hongchuan; Yan, Xiao; Duan, Xiaoxiang; Dong, Jinyan (Frontiers in Microbiology, 2018)
Fungal endophytes live widely inside plant tissues and some have been revealed to provide benefits to their host and ecological environment. Considering the fact that endophytes are engaged in remarkably stable long-term interactions with their host for the whole of their life cycle, it’s conceivable that both partners have substantial influence on each other’s metabolic processes. Here, we investigated the fermented products of an endophytic fungus Umbelopsis dimorpha SWUKD3.1410 grown on host-plant Kadsura angustifolia and wheat bran, respectively, to assess the impact of SWUKD3.1410 on the secondary metabolites of K. angustifolia. Twenty compounds (1-20) were isolated and classed into eleven schitriterpenoids (1-9, 17-18), two lignans (10, 20), two sesquiterpenoids (11-12), one trinorsesquiterpenoid (13), one monoterpene (14), one sterol (19), and two simple aromatic compounds (15-16) by the extensive 1D-, 2D-NMR and HR-ESI-MS data analysis. Except for nigranoic acid (1), compounds 2-19 have never been found before from K. angustifolia. Of them, metabolites 2, 11 and 14 were identified to be new. Obtained results indicated that U. dimorpha SWUKD3.1410 can significantly produce the same/similar components as its host, modify the host-plant components, but also enhance the production of those highly oxygenated schitriterpenoids/schinortriterpenoids in plants. This study suggested a prospective feasibility for setting up alternative processing techniques to boost the quality of crude drugs derived from K. angustifolia and add their values.